Pengaruh Kualitas Layanan PT Perempatan Event Organizer terhadap Kepuasan Peserta Rapat Dinas Lintasarta Bali 2023 - Rany Inggriany Br Sagala; Safaruddin Safaruddin (JURNAL RISET MANAJEMEN (JURMA), 2024)
The MICE (Meeting, Incentive Convention, Exhibition) industry is the entry point for introducing tourism and in the end it becomes a special interest tourism destination and tourism actors are starting to develop MICE destinations as superior destinations because they have a multiplier effect on increasing the economy of a region. Making it easier for domestic and international tourists to travel to the island of Bali. PT Perempatan EO Bali is a service business that provides services in the field of MICE events and is the organizer of the Lintasarta Bali 2023 event. Judging from the quality of service, PT Perempatan EO always provides the best service in terms of reliability, responsiveness, physical evidence, guarantees, and empathy. The company also always provides professional and reliable services and guarantees the satisfaction of participants in the Lintasarta Bali 2023 official meeting event. This research uses a quantitative research type. The object of this study were participants in the 2023 Bali cross-art service meeting, where the research instrument was a questionnaire. In this study, a saturated sample was used, which consisted of 109 cross-section event participants. The data analysis technique used in this study is multiple linear regression analysis, classical assumption test, hypothesis testing (t test, f test, and analysis of the coefficient of determination test). The results of this study indicate that the quality of service simultaneously has a positive and significant effect on the satisfaction of participants in the 2023 Bali cross-art agency meeting with an f-count value greater than f-table, namely 48.119> 3.93. The variable Reliability partially has a positive and significant effect on the satisfaction of participants in the 2023 Bali cross-art agency meeting with the results of t-count (2,302) greater than t-table (1,983), the responsiveness variable has a positive and significant effect on the satisfaction of participants in the 2023 Bali cross-art service meeting with the results of t-count (3.075) are greater than t-table (1.983), the variable physical evidence has a positive and significant effect on the satisfaction of participants in the 2023 Bali cross-art agency meeting with the results of t-count (3.329) greater than t-table (1.983), the guarantee variable has a positive and significant effect on the satisfaction of participants in the 2023 Bali cross-art agency meeting with the result t-count (5.044) greater than t-table (1.983)